2022
DOI: 10.1111/acel.13734
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products induce senescence of atrial myocytes and increase susceptibility of atrial fibrillation in diabetic mice

Abstract: Diabetes mellitus (DM) is a common chronic metabolic disease caused by significant accumulation of advanced glycation end products (AGEs). Atrial fibrillation (AF) is a common cardiovascular complication of DM. Here, we aim to clarify the role and mechanism of atrial myocyte senescence in the susceptibility of AF in diabetes. Rapid transesophageal atrial pacing was used to monitor the susceptibility of mice to AF. Whole‐cell patch‐clamp was employed to record the action potential (AP) and ion channels in singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…When telomeres shorten and become inactive, cells interpret this as a break in the DNA strand and respond by activating the p53/p21 CIP1/WAF1 pathway, causing cell-cycle arrest and inducing replicative senescence [ 26 , 28 ]. AGEs can induce cellular senescence in endothelial cells [ 29 ] and atrial myocytes [ 30 ]. Resveratrol has been shown to prevent high-glucose-induced cellular senescence in cultured human diploid fibroblasts [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…When telomeres shorten and become inactive, cells interpret this as a break in the DNA strand and respond by activating the p53/p21 CIP1/WAF1 pathway, causing cell-cycle arrest and inducing replicative senescence [ 26 , 28 ]. AGEs can induce cellular senescence in endothelial cells [ 29 ] and atrial myocytes [ 30 ]. Resveratrol has been shown to prevent high-glucose-induced cellular senescence in cultured human diploid fibroblasts [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of AF in individuals with diabetes may be attributed to factors such as left atrial enlargement, interstitial fibrosis in the atrial myocardium, and electrical remodeling [ 38 , 39 ]. Moreover, findings from an in vitro study found a potential link between advanced glycation end products and heightened atrial myocyte senescence, contributing to a susceptibility to AF [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, senescent cells may be a major cause and consequence of tissue damage and abnormal metabolic changes, central to the pathogenic circuit of diabetes 8 . The diabetic microenvironment also promotes CS 9 . Recent studies have shown that hyperinsulinemia leads to a premature senescent transcriptomic and secretory profile in mature adipocytes, 10 while also causing insulin resistance in neurons, which results in a senescence‐like phenotype 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 The diabetic microenvironment also promotes CS. 9 Recent studies have shown that hyperinsulinemia leads to a premature senescent transcriptomic and secretory profile in mature adipocytes, 10 while also causing insulin resistance in neurons, which results in a senescence‐like phenotype. 11 Additionally, recent research indicates that sustained hyperinsulinemia contributes to the senescence of hepatocytes.…”
Section: Introductionmentioning
confidence: 99%